Experimental intracerebral hemorrhage: avoiding pitfalls in translational research - Kirkman, Matthew A (Nature Publishing Group, 2011)
Intracerebral hemorrhage (ICH) has the highest mortality of all stroke subtypes, yet treatments are mainly limited to supportive management, and surgery remains controversial. Despite significant advances in our understanding of ICH pathophysiology, we still lack preclinical models that accurately replicate the underlying mechanisms of injury. Current experimental ICH models (including autologous blood and collagenase injection) simulate different aspects of ICH-mediated injury but lack some features of the clinical condition. Newly developed models, notably hypertension- and oral anticoagulant therapy-associated ICH models, offer added benefits but further study is needed to fully validate them. Here, we describe and discuss current approaches to experimental ICH, with suggestions for changes in how this condition is studied in the laboratory. Although advances in imaging over the past few decades have allowed greater insight into clinical ICH, there remains an important role for experimental models in furthering our understanding of the basic pathophysiologic processes underlying ICH, provided limitations of animal models are borne in mind. Owing to differences in existing models and the failed translation of benefits in experimental ICH to clinical practice, putative neuroprotectants should be trialed in multiple models using both histological and functional outcomes until a more accurate model of ICH is developed.